EKSTRAK BIJI BUAH PINANG SEBAGAI PEWARNA ALAMI PADA KAIN SASIRANGAN - Prabawa, I Dewa Gede Putra (Kementerian Perindustrian, 2015)
The research about utilization of extracts areca nuts (Areca catechu L.) as natural dye on sasirangan using whiting mordan 1% (w/v) was carried out. The results showed that the extract of areca nuts can be used as a dye on sasirangan with the types of cloth ware cotton, silk, semi-silk and the colour was red guava. The dye yield of areca nuts was resulted in 34.43%. The optimum mass of natural dye on cotton was adsorbed about 1,90% in the concentration of dye solution 1:50 (g/mL), on silk about 0,46% in the concentration of dye solution 1:100 (g/mL), and on semi-silk about 0,64% in the concentration of dye solution 1:75 (g/mL). The quality color fastnessin detergents 1% were showed the best value on cotton about 23% in the concentration of dye solution 1:50 (g/mL), on silk about 66% in the concentration of dye solution 1:75 (g/mL), and on semi-silk about 34% in the concentration of dye solution 1:100 (g/mL). The results of dray and wet brush resistance showeda good values for all treatment with the avaregge staining scale values were 3-4. The qualities of color intensity for cotton and silk showed that the higher mordant concentration, washing fastness becomes better, and color is deeper. The quality of color intensity optimum for semi-silk was showedÂ in the concentration of dye solution 1:75 (g/mL). The optimal result for cotton is in the used of day solution 1: 100 (g/mL), silk 1:75 (g/mL), and semi-silk 1:75 (g/mL) which the whiting mordant concentration was used 1% for all treatment.Keywords: arace nuts (Areca catechu L.), whiting mordant, sasirangan dyeing